Updates in the Understanding and Management of Thyroid Cancer - Fahey, Thomas J. (IntechOpen, 2012)
Thyroid cancer can be either common or rare, and takes several forms in multiple populations, such as children and adolescents. The chapters in this book, which provide state-of-the-art knowledge in understanding and treating the condition, are therefore welcome. Our understanding of thyroid cancer is advanced by several chapters on its incidence in a Spanish population, the functionality of p53 and the use of microarray technology in research. Diagnostic issues include the roles of glycosylation and glycoproteins, and use of a γ-camera to evaluate the in vivo biodistributions and internal medical dosimetries of Iodine-131. The majority of chapters address the range of possible treatment protocols, such as IGF signalling, surgical management, sentinel lymph node biopsy, radioiodine treatment and differentiation therapy.